Rainlily, Zephyranthes and Habranthus spp.: Low Maintenance Flowering Bulbs for Florida Gardens: ENH1151/EP412, 11/2009 - Knox, Gary W. (EDIS, 2010)
ENH1151, a 12-page illustrated fact sheet by Gary W. Knox, describes these small flowing bulbs that flower within a few days after a rainfall — where to plant them, how to care for them, how to propagate them, and common species and selections. Includes references. Published by the UF Department of Environmental Horticulture, November 2009. ENH1151/EP412: Rainlily, Zephyranthes and Habranthus spp.: Low-Maintenance Flowering Bulbs for Florida Gardens (ufl.edu)